2016
DOI: 10.1159/000450551
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis and Body Mass Index Predict Hepatocarcinogenesis following Eradication of Hepatitis C Virus RNA by Direct-Acting Antivirals

Abstract: Background and Aims: Predictive factors for hepatocarcinogenesis following eradication of hepatitis C virus (HCV) RNA by antiviral therapy with direct-acting antivirals are unknown. Especially the impact of treatment with or without interferon on hepatocarcinogenesis is not clear. Methods: A total of 958 patients with HCV genotype 1-related chronic liver disease and a sustained virological response defined as negative HCV RNA 24 weeks after cessation of antiviral therapy with direct-acting antivirals (triple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In the present study, the estimated annual incidence of HCC for the first 2 years under all-oral direct-acting antiviral regimens was 0.9%. We have also shown that the HCC rate following direct-acting antiviral regimens was not different from that following interferon treatment in patients who achieved SVR [24,25] . In the present study, we compared HCC development rates between direct-acting antiviral regimens ( n = 1,065) and 24 weeks of NS3/4A protease inhibitor (telaprevir or simeprevir)/peginterferon/ ribavirin regimens ( n = 331) in patients who achieved SVR.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the present study, the estimated annual incidence of HCC for the first 2 years under all-oral direct-acting antiviral regimens was 0.9%. We have also shown that the HCC rate following direct-acting antiviral regimens was not different from that following interferon treatment in patients who achieved SVR [24,25] . In the present study, we compared HCC development rates between direct-acting antiviral regimens ( n = 1,065) and 24 weeks of NS3/4A protease inhibitor (telaprevir or simeprevir)/peginterferon/ ribavirin regimens ( n = 331) in patients who achieved SVR.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies from our laboratories showed that SVR, regardless of the type of treatment, reduced the chance of development of HCC [24,25] . Our study also determined the cumulative HCC rate and the risk factors for HCC in patients under treatment with all-oral combinations of direct-acting antiviral regimens.…”
Section: Discussionmentioning
confidence: 92%
“…Further studies should be performed to evaluate the relationship between CAP and lipid metabolism. Interestingly, clinical evidence suggest a link between obesity and HCC after SVR, but body weight was not measured regularly in the present study. Considered with the above findings, further studies are required to investigate the relation between changes in CAP following DAA treatment and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have established the correlation between the degree of liver fibrosis and HCC [19, 20]. Cirrhotic patients with complications are in decompensated states.…”
Section: Discussionmentioning
confidence: 99%